Development of emotional and behavioral problems in neurofibromatosis type 1 during young childhood. Issue 9 (19th June 2017) - Rietman, André B.; Oostenbrink, Rianne; van Noort, Kimberley; Franken, Marie‐Christine J. P.; Catsman‐Berrevoets, Coriene E.; Aarsen, Femke K.; Hendriksen, Jos G.; de Nijs, Pieter F. A.
Abstract : This retrospective longitudinal study in young children with neurofibromatosis type 1 (NF1) aimed to identify if, and how early problems in behavior, intelligence, and language development are associated with later behavioral problems. At the first assessment at preschool age, we evaluated language skills, intelligence, and emotional and behavioral problems as reported by parents. The second assessment at school‐age we evaluated intelligence, and emotional and behavioral problems as reported by parents and teachers. Association of baseline assessments with secondary assessment was evaluated using multivariable linear regression analysis. Of the 61 patients (25 males, 36 females; mean age 4;5 years [SD 1;1 years]) with NF1 who had a first assessment, 38 children (21 males, 17 females; mean age 7;11 years [SD 2;1 years]) had a second assessment after a mean period of 3;5 years. Longitudinal data on behavioral problems were collected for 23 of these children. Intelligence and language development were not associated with internalizing problems. Parent‐rated internalizing behavioral problems significantly increased with age in this subgroup. Baseline internalizing problems predicted later internalizing problems (adjusted R 2  = 0.33, p  = 0.003). The presence of these problems at pre‐school age may be predictive of internalizing problems at a later age.